Digital Sarcasm as Social Critique: A Pragmatic and Cyberpragmatic Analysis of Social Media Reactions (e-Journal of Linguistics, 2025)
This study investigates the use of sarcasm in social media comments responding to the comparison of corruption punishments in Indonesia and China. Using a qualitative approach with pragmatics and cyberpragmatics frameworks, the research identifies and analyzes the forms, functions, and contexts of sarcasm in digital discourse. Data were collected from high-engagement comments on platforms like Instagram and Twitter, focusing on posts criticizing the disparity in corruption sentences. Linguistic indicators such as hashtags, emojis, capital letters, and exclamation marks were observed, revealing sarcasm's role in conveying dissatisfaction. Pragmatically, comments served as tools for social critique, emphasizing protest against legal injustices and invoking moral values like fairness and transparency. Cyberpragmatically, the digital context amplified the emotional tone and increased the viral potential of the comments, enabling broader public discourse. This study highlights sarcasm's effectiveness as a means of public criticism, demonstrating how digital platforms facilitate creative and collective expressions of social dissatisfaction.
Keywords: Sarcasm; pragmatics; Cyberpragmatics; Social Media; Corruption Pusnishment